Pengaruh Pemanfaatan Aplikasi Penilaian Kinerja Guru Terhadap Peningkatan Profesionalisme Guru - FR.R. Dewi Astika Indah Sintawati; Hermanu Joebagio; Leo Agung Sutimin (Universitas Sebelas Maret, 2018)
The evaluation of teachers’ performance is getting crucial to find out the degree of their professionalism. The education institution has to be able to figure out what factors may influence the teachers’ performance. The analysis result will be useful in developing their human resources in an optimum way which is very needed to promote the education’s quality. They need certain attention from the government and people. As the matter of fact above, the government has regulated the enhancement of educators’ quality or teachers in national perspective through the law No 20 in the year of 2003 about national education system. It is still done conventionally which has a big effect on their professionalism. This research has a purpose to set up an application of teacher performance evaluation in order to gain their performance and professionalism. It is used a method namely research and development consisting of 10 steps which are modified to result on teacher performance evaluation in line with teachers’ professionalism improvement. The final result of development comes to the application teacher performance evaluation with computer based containing evaluation components such as; personality, pedagogy, professional, social and the overall score which enables to Improve teachers’ professionalism at the maximum point. The research result shows that the developed application has completed the feasibility requirements to be used as an application system of teacher performance evaluation process. It can be seen from the data of material expert with the average score of 4,4 as categorized very good. While the media expert validation shows the score of 4,5 with the category of very good. According to the assessor shows that this teacher performance evaluation coming to score of 4,6 with the category of very good. At the effectiveness test, it shows that the average score of experiment class which is 82,9178 is higher compared with control class at the average score of 61, 26363.